Features of the social beliefs of the Orthodox Church and Christians of the Evangelical Faith - Микола Стадник; Владислав Харченко (Cхід)
The article examines the peculiarities of social beliefs of the Orthodox Church and Christians of the Evangelical Faith and their reflection in educational practices. It is shown that the formation of social doctrines is one of the basic tasks of modern Christianity. Social doctrine systematizes and actualizes the role and significance of social beliefs of Christianity, in their essence multi-vector, multi-dimensionality, inte-gration as the main characteristics of the spiritual sphere of the church. Social doc-trines are based on various aspects of theological and ecclesiological beliefs. They can be expressions of the theological tradition’s response to historical problems, social transformations of the digital age, in the confessional discourse, and can also reflect the modern view of a certain church on the issue of the relationship between faith and reason, science and religion, and humanitarian security. Approaches to social beliefs may differ depending on the "confessional color" of a certain religious organization and the information support of this process. According to this study, the implementation of the social doctrines of Christianity is impossible without an analysis of their beliefs aimed at solving both social issues in general and educa-tional ones. The need to develop basic strategies of spiritual education is empha-sized, outline the priorities facing education in a secularized world, but also suggest the development of sustainable concepts in the direction of highlighting the confes-sional worldview regarding the challenges of modern humanitarianism. It is proposed to consider the peculiarities of social beliefs in the system of educational processes of the Orthodox Church and the Christian Church of the Evangelical Faith. The con-clusions emphasize that the social doctrine of the Ecumenical Patriarchate presup-poses a progressive attitude to science and technological progress, encourages the church to use the resources of technological progress and informational resources for preaching. The need for the introduction of an integrated approach in spiritual education, constant informational innovations in the field of training of qualified min-isters who are able to conduct missionary preaching activities taking into account the conditions of the time for an efficient educational process and humanitarian security in the context of transformations of the digital age is being updated.